COVID-19 and liver cancer: lost patients and larger tumours. Issue 1 (21st April 2022) - Geh, Daniel; Watson, Robyn; Sen, Gourab; French, Jeremy J; Hammond, John; Turner, Paul; Hoare, Tim; Anderson, Kirsty; McNeil, Michael; McPherson, Stuart; Masson, Steven; Dyson, Jessica; et al.
Abstract : Background: Northern England has been experiencing a persistent rise in the number of primary liver cancers, largely driven by an increasing incidence of hepatocellular carcinoma (HCC) secondary to alcohol-related liver disease and non-alcoholic fatty liver disease. Here we review the effect of the COVID-19 pandemic on primary liver cancer services and patients in our region. Objective: To assess the impact of the COVID-19 pandemic on patients with newly diagnosed liver cancer in our region. Design: We prospectively audited our service for the first year of the pandemic (March 2020–February 2021), comparing mode of presentation, disease stage, treatments and outcomes to a retrospective observational consecutive cohort immediately prepandemic (March 2019–February 2020). Results: We observed a marked decrease in HCC referrals compared with previous years, falling from 190 confirmed new cases to 120 (37%). Symptomatic became the the most common mode of presentation, with fewer tumours detected by surveillance or incidentally (% surveillance/incidental/symptomatic; 34/42/24 prepandemic vs 27/33/40 in the pandemic, p=0.013). HCC tumour size was larger in the pandemic year (60±4.6 mm vs 48±2.6 mm, p=0.017), with a higher incidence of spontaneous tumour haemorrhage. The number of new cases of intrahepatic cholangiocarcinoma (ICC) fell only slightly, with symptomatic presentation typical. Patients received treatment appropriate for their cancer stage, with waiting times shorter for patients with HCC and unchanged for patients with ICC. Survival was associated with stage both before and during the pandemic. 9% acquired COVID-19 infection. Conclusion: The pandemic-associated reduction in referred patients in our region was attributed to the disruption of routine healthcare. For those referred, treatments and survival were appropriate for their stage at presentation. Non-referred or missing patients are expected to present with more advanced disease, with poorer outcomes. While protective measures are necessary during the pandemic, we recommend routine healthcare services continue, with patients encouraged to engage.